Influence of Timber Moisture Content on the Ultrasonic Wave Velocity Measurement of Tectona grandis L.F. and Cupressus lusitanica M. from Costa Rica - Paniagua Hernández, Viviana (2022)
Ultrasound is a reliable non-destructive method commonly used to evaluate the state of a piece of wood. The effect of the moisture content (MC) on the timber wave velocity, which is different de-pending on the wood species, must be considered. MC adjustment factors are important if accurate and comparable results are to be achieved. Thus, the goal of this study is to define a model that allows obtaining the adjustment factor to predict the standard velocity (12% of MC (V12) from ve-locity obtained at different MC for two Costa Rican commercial species: Tectona grandis L.F (teak) and Cupressus lusitanica M. (cypress). This effect was studied on small clean specimens during the desorption stages, from the fiber saturation point to the oven-dry state, controlling the specimen’s mass and MC on 62 specimens. With this data, the rate of change in ultrasound velocity per MC was modeled. Thus, the applicability of already published moisture adjustment models for conifers and hardwood tropical species was proved. The results showed that the proposed model coefficients adjust better than the ones obtained from the wood science literature, which makes them suitable to describe ultrasound velocity in different moisture conditions (VH).